YAŞLANMANIN PLAZMA OKSİDATİF PROTEİN HASARINA ETKİSİ - ÇAKATAY, Ufuk; TELCİ, Ayşegül and YILMAZ, İlker and AKÇAY, Tülay and SİVAS, Ahmet (Cerrahpaşa Medical Journal, 2019)
Background and Design.- An increase in oxidative stress may contribute to the development of oxidative protein damage in aging. In the present study, we investigated the relation between aging and oxidative protein damage parameters such as plasma protein carbonyl and protein thiol, as well as oxidative stress parameters such as total thiol, nonprotein thiol and lipid hydroperoxides in the plasma samples of young adult, adult and young old individuals. Results.- Protein carbonyl and lipid hydroperoxide levels were significantly increased in aging individuals. On the other hand, total thiol and protein thiol levels were significantly decreased in aging individuals. Protein carbonyl, protein thiol, and lipid hydroperoxide levels were significantly correlated with age. Conclusion.- The result of this study suggests that increased plasma protein carbonyl levels and decreased plasma protein thiol levels in aging individuals may reflect the oxidative protein damage.